2020
DOI: 10.1001/jamanetworkopen.2020.14323
|View full text |Cite
|
Sign up to set email alerts
|

Association of a Public Health Campaign About Coronavirus Disease 2019 Promoted by News Media and a Social Influencer With Self-reported Personal Hygiene and Physical Distancing in the Netherlands

Abstract: IMPORTANCE In the absence of a vaccine and therapeutic agent, personal hygiene and physical distancing are essential measures to contain the coronavirus disease 2019 pandemic. OBJECTIVE To determine whether a social media campaign, targeted at the gaps in behavior on personal hygiene and physical distancing and distributed nationwide via digital news media, may be an effective method to improve behavior and help to inhibit person-to-person transmission of severe acute respiratory syndrome coronavirus 2. DESIGN… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
48
0
1

Year Published

2020
2020
2023
2023

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 61 publications
(54 citation statements)
references
References 12 publications
(20 reference statements)
1
48
0
1
Order By: Relevance
“… 23 , 33–38 With the exception of one study that only reported 777 869 Twitter ‘tweets’, 37 the mean number of participants in each study was 5293 (standard deviation = 9105), with median number of 1625 participants (range = 482–37 077). Most studies used cross-sectional survey designs ( k = 22), whereas other design types included longitudinal surveys ( k = 3), 14 , 23 , 38 quasi-experimental ( k = 1), 17 experimental designs ( k = 2) 21 , 32 and media analysis ( k = 1). 37 Convenience sampling methods were used in almost all included studies ( k = 14 convenience samples and k = 13 stratified convenience samples), with the exception of two studies that relied on random sampling 14 and quota sampling 34 methods.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“… 23 , 33–38 With the exception of one study that only reported 777 869 Twitter ‘tweets’, 37 the mean number of participants in each study was 5293 (standard deviation = 9105), with median number of 1625 participants (range = 482–37 077). Most studies used cross-sectional survey designs ( k = 22), whereas other design types included longitudinal surveys ( k = 3), 14 , 23 , 38 quasi-experimental ( k = 1), 17 experimental designs ( k = 2) 21 , 32 and media analysis ( k = 1). 37 Convenience sampling methods were used in almost all included studies ( k = 14 convenience samples and k = 13 stratified convenience samples), with the exception of two studies that relied on random sampling 14 and quota sampling 34 methods.…”
Section: Resultsmentioning
confidence: 99%
“…Only three studies investigating the effects of interventions on attitudes or adherence to COVID-19 public health recommendations were identified in this review. Yousuf et al 17 conducted an uncontrolled experimental study using convenience samples ( n = 16 072 [diagnostic survey] and n = 17 189 [post-campaign survey]) in the Netherlands. They report that exposure to both a targeted video campaign featuring a 22-year-old male social media influencer and a related newspaper article with infographics improved handwashing duration and thoroughness.…”
Section: Resultsmentioning
confidence: 99%
“…The overall improvement in hygiene practices in KSA during this pandemic reflects the effectiveness of the early and efficient health education campaigns through media and telecommunication tools such as Short Message Service (SMS). Yousuf et al 17 found that exposure to a targeted public health campaign about COVID-19 using social media platforms and digital news was associated with an increase in the odds of washing all required areas in hands as well as longer hand-washing duration in the Netherlands.…”
Section: Discussionmentioning
confidence: 99%
“…To date, there is no vaccine or definite medication for COVID-19; therefore, physical distance and personal hygiene are essential for containing this pandemic. 17 Thus, the aim of this study is to assess the current personal hygiene practices and to test the effect of COVID-19 pandemic in improving these practices compared to the pre-pandemic era among individuals living in KSA.…”
mentioning
confidence: 99%
“…According to the abovementioned report [3], there were 465,166 cases and 27,878 deaths in Brazil. In past pandemic outbreaks, information exchange was relatively slow. However, with the popularization of the internet, 3.7 billion people worldwide (approximately 49.7% of the world's population) commonly use web-based information [4], and these people rely on two main sources of web-based data, namely news media web sites and social media. Using these media, people keep themselves informed about treatments, prevention, and cases, and they also participate in debates about the impact of the COVID-19 outbreak on their lives.…”
Section: Introductionmentioning
confidence: 99%